Fatigue Detection of XYZ Drivers based on Human Brain Wave EEG Signals - Shabrina Choirunnisa; Beni Widiawan; I Gede Wiryawan; Agus Purwadi; Yogiswara Yogiswara; Bekti Maryuni Susanto (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2022)
The cause of death due to traffic accidents isnow increasingly common. One of the main factors causing thisaccident is driver fatigue. This can happen because the driveris not aware of his tired mental state. Of course mental fatiguecan cause a lack of concentration while driving. This mentalfatigue can be detected by analyzing the brain waves throughthe EEG signal from the driver. This brain wave analysis canbe done by various methods. In this study, the authorsconducted a brain wave-based detection of mental fatigueusing the Fourier transform and Support Vector Machine. TheEEG signal data will be feature extracted using the FourierTransform. Then, the results of this extraction will be used forthe classification process with the Support Vector Machinemethod. Based on the experimental results, the classification ofmental fatigue using a Support Vector Machine with a linearkernel obtained an average accuracy of 85%.